FINANCIAL PERFORMANCE ANALYSIS OF RURAL BANKS IN MANOKWARI: A CASE STUDY OF ARFAK INDONESIA RURAL BANK - Rully Novie Wurarah; Mona Permatasari Mokodompit (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
The purpose of this research is to analyse the financial performance of Arfak Indonesia Rural Bank in Manokwari Regency in the period of 2014 – 2018 using financial ratios include liquidity, solvency and profitability ratios. Liquidity ratio is measured using Loan to Deposit Ratio (LDR), solvency is measured using Capital Adequacy Ratio (CAR), and profitability ratio is measured using Net Profit Margin (NPM) and Return on Asset (ROA). The research results shows that in the past 5 years, the average value of LDR (113%) is too high which is above 80%, thus the bank does not have enough liquidity to cover any unforeseen fund requirement. Furthermore, the average value of CAR (10.67%) was between the value of 9.5% and 11%, which indicates that the bank has enough capital to cushion potential losses and protect depositor’s money. As for the average value of NPM (39.46%) and ROA (6.73%) shows that the bank has a very good ability in generating profits.